Fungal Discospondylitis in a White Swiss Shepherd Bitch Caused by Aspergillus sp. - Smaili Santos, Iago; de Lima Bernardes, Giselle; Nogueira Smanioto, Danilo; Garcia Pretto-Giordano, Lucienne; Bahr Arias, Mônica Vicky (Acta Scientiae Veterinariae, 2025)
Background: Several infectious agents can cause discospondylitis, primarily due to hematogenous dissemination, with bacterial infection being the most common. Fungal discospondylitis is rare and can result from infection by various agents, including Aspergillus spp. Disseminated aspergillosis, which may cause discospondylitis, is more prevalent in German Shepherd dogs, possibly due to genetic defects in cellular and humoral immune responses. Given the rarity of this condition, the aim of this report is to describe a case of fungal discospondylitis in a young White Swiss Shepherd bitch caused by Aspergillus sp. Case: A 1-and-a-half-year-old White Swiss Shepherd bitch was presented with a history of acute-onset paraparesis that progressed to paraplegia. Neurological examination revealed grade IV thoracolumbar syndrome, characterized by paraplegia with loss of superficial sensation in the pelvic limbs, absence of the cutaneous trunk reflex caudal to the 6th thoracic vertebra, and pain on manual palpation of the spine at T4/T5/T6. Radiographs of the thoracic spine were performed, but the results were inconclusive, leading to referral for computed tomography (CT). CT revealed lytic areas in the T4-T5 vertebral bodies and a presence of an amorphous structure with soft tissue density in the extradural space at T4/T5, causing spinal cord compression, consistent with a diagnosis of discospondylitis. Abdominal ultrasound and urine culture were conducted to investigate the primary source of infection, but the results were inconclusive. The patient’s condition deteriorated despite antibiotic therapy, leading to cerebrospinal fluid analysis and hemilaminectomy for spinal cord decompression and collection of disc material between T4/T5 for fungal and bacterial culture. The fungal culture of the granuloma and disc material was positive for Aspergillus sp. Consequently, antibiotic therapy was discontinued, and treatment with itraconazole was started. Two months after starting antifungal treatment, there was no improvement in the neurological and clinical condition, and the patient was euthanized. Discussion: Most reports of aspergillosis in dogs in Brazil involve the respiratory tract; therefore, the case described in this study is likely the 1st report of fungal discospondylitis caused by Aspergillus sp. in a canine in the country. German Shepherd dogs and their variations, such as the White Swiss Shepherd, may be more susceptible to fungal infection by Aspergillus spp. due to an inherited immunological defect related to lower levels of immunoglobulin A. Discospondylitis can be diagnosed by radiographic examination; however, in this patient, no endplate lysis or bone proliferation was observed, which could occur in the early stages of the disease, as radiographic changes can take 2 to 6 weeks to appear. Therefore, advanced imaging, such as computed tomography, was necessary. Given that bacterial discospondylitis is much more common than fungal infection, antibiotic therapy was initiated, but without improvement in the condition, leading to the collection of disc material for microbiological analysis. Hence, it is important to include fungal discospondylitis and disseminated aspergillosis in the differential diagnosis for German Shepherd dogs and their variations with rapidly progressive spinal syndromes that do not respond to antibacterial treatment. Keywords: canine, mycose, aspergillosis, Aspergillus spp., discoespondylites, White Swiss Shepherd. Título: Discoespondilite fúngica em uma cadela Pastor Suíço Branco causada por Aspergillus sp. Descritores: canino, micose, aspergilose, Aspergillus spp., discoespondilite, Pastor Branco Suíço.